RHETORICAL ANALYSIS OF STAND-UP COMEDY PERFORMANCES BY THREE FAMOUS AMERICAN COMICS - Fadly Dzil Ikram; Safnil Arsyad; Gita Mutiara Hati (Journal of English Education and Teaching, 2018)
This research aimed at finding the rhetorical of narrative section based on Labov’s model and the stand-up comedy techniques which dominantly used by Jim Jefferies, Ricky Gervais, and Bill Burr on their performances. The observation checklist was used in this research. Fifteen different topics performance from each stand-up comedian were analyzed by using descriptive method, using quantitative as well as qualitative data. From the result it was found that three stand-up comedians used narrative section suggested by Labov. The narrative section is abstract, orientation, complicating actions, resolution, and coda. Also, the most frequent techniques used by three stand-up comedians are rule of three and one liner technique. Those techniques are the most effective technique that can trigger audience laughter. The last finding of this research, there are two common patterns created by three stand-up comedians based on Labov’s model of narrative sections.